TRANSLATING FEMINISM - Gajewska, Agnieszka (WUJ, 2012)
Translating feminism Pointing to manifold and long-lasting connections between feminism and translation, the article ﬁrst presents a selection of multilingual writers (Narcyza Żmichowska and Deborah Vogel), translators (Zoﬁa Żeleńska and Kazimiera Iłłakowiczówna) and translation commentators (Joanna Lisek and Karolina Szymaniak) to ponder why the work of early Polish feminists is neglected. It seems that one of the reasons might be the current colonization of Polish feminist discourse by English. For ethical reasons it would be advisable to recommend a certain sensitivity to locality in feminist translation studies and a recognition of regionalism in culture studies. The theoretical considerations include two issues: the potential hermaphroditism of the Polish language when its users are women and the ‘scandal of „another’s speech”,’ a polyphony and a constitutive lack of autonomy (a feminist discussion of Mikhail Bakhtin’s theory). From this perspective it becomes visible that linguistic choices made by the translator are always individual one-time solutions which resist homogenization, paradigms or (theoretical) generalizations.
Keywords: feminism; translation studies; regionalism of cultural studies; interlingual transgression